Patient with Von Hippel-Lindau disease diagnosed with Renal Cell Carcinoma (Research, Society and Development, 2024)
Von Hippel-Lindau disease is an autosomal dominant hereditary disorder caused by a germline mutation in the VHL gene. Those mutations lead to the development of multiple benign and malignant tumors, including renal cell carcinoma (RCC). VHL disease is the most common risk factor for hereditary RCC, presenting in 1 in 36,000 live births. Patients with VHL disease are at high risk of early and multiple clear cell RCC; approximately two-thirds will present several renal cysts and RCC during their lifetimes. RCCs are the leading cause of death in patients with VHL, and median overall survival in these patients is around 50 years. The purpose of the present study is to present a clinical case report of a 54-year-old Indonesian male patient who had a stiff neck, followed by constant tingling in the right arm. The patient was subsequently diagnosed with VHL disease based on clinical diagnostic criteria, which included central nervous system (CNS) hemangioblastoma, pancreatic cyst, and RCC. Early recognition and treatment remain the mainstay of VHL disease management. Treatment decisions for RCC in VHL depend on tumor size and growth kinetics of each lesion, as those parameters determine the risk of metastatic disease. The main therapeutic goal to deal with RCCs in patients with VHL disease is to remove as many RCCs as possible while preserving renal function.